DOI: 10.11606/d.3.2014.tde-23122014-154428
|View full text |Cite
|
Sign up to set email alerts
|

Comparação termodinâmica e ambiental (emissões de CO2) das rotas de produção e utilização de combustíveis veiculares derivados de petróleo e gás natural, biocombustíveis, hidrogênio e eletricidade (veículos elétricos).

Abstract: , por me permitir desenvolver este trabalho como participante da sua equipe de pesquisa, pelas orientações e o apoio no desenvolvimento das atividades do curso, por acreditar nas minhas capacidades, e pelas oportunidades para expor as minhas ideias e corrigir os meus erros, sempre fazendo uso do bom humor e seu trato amável com as pessoas que lhe rodeiam.À minha mãe, Gloria Orrego-Vélez e ao meu pai Jaime Flórez-Palacio, pelo suporte, o carinho, a compreensão e a repreensão, a confiança durante toda a minha vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(165 reference statements)
0
4
0
Order By: Relevance
“…Based on the thermoeconomy theories [40][41][42][43][44][45][46], the authors [47][48][49][50][51] have shown that exergoeconomy provides an opportunity to quantify the renewable and non-renewable, specific exergy consumption; to properly allocate the associated CO2 emissions among the streams of a given production route; as well as to determine the overall exergy conversion efficiency of the production processes. According to [49][50][51], the nonrenewable unit exergy cost (cNR) [kJ/kJ] is defined as the rate of non-renewable exergy necessary to produce one unit of exergy rate/flow rate of a substance, fuel, electricity, work or heat flow, whereas the Total Unit Exergy Cost (cT) includes the Renewable (cR) and Non-Renewable Unit Exergy Costs. Analogously, the CO2 emission cost (cCO2) [kmolCO2/kJ] is defined as the rate of CO2 emitted to obtain one unit of exergy rate/flow rate.…”
Section: Exergy Cost Balancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the thermoeconomy theories [40][41][42][43][44][45][46], the authors [47][48][49][50][51] have shown that exergoeconomy provides an opportunity to quantify the renewable and non-renewable, specific exergy consumption; to properly allocate the associated CO2 emissions among the streams of a given production route; as well as to determine the overall exergy conversion efficiency of the production processes. According to [49][50][51], the nonrenewable unit exergy cost (cNR) [kJ/kJ] is defined as the rate of non-renewable exergy necessary to produce one unit of exergy rate/flow rate of a substance, fuel, electricity, work or heat flow, whereas the Total Unit Exergy Cost (cT) includes the Renewable (cR) and Non-Renewable Unit Exergy Costs. Analogously, the CO2 emission cost (cCO2) [kmolCO2/kJ] is defined as the rate of CO2 emitted to obtain one unit of exergy rate/flow rate.…”
Section: Exergy Cost Balancesmentioning
confidence: 99%
“…It is also important to notice that, since this first approach deals with a basically fossil-based ammonia production process, the advantages of the cost splitting seem not to be initially so evident. However, reported data on exergy costs and CO2 emission cost of various fuels [47][48][49][50][51] have shown that a small part of the cumulative unit exergy costs of natural gas and petroleum derivatives corresponds to renewable sources and, thus, it must be accounted for if a fair level playing field for comparative assessments with other syngas and ammonia production technologies is intended. For instance, other scenarios, including the syngas production by using the steam reforming of ethanol, have earned more attention in Brazil, mainly due to its well-established sugar cane ethanol economy [111][112][113][114][115].…”
Section: Cumulative Unit Exergy Costs and Co2 Emission Costmentioning
confidence: 99%
“…It is clear that a lot more exergy is destroyed within the power generation unit in all configurations. This makes sense considering the combustion process inevitably destroys at least one fourth of the exergy [116]. The S-Graz cycle seems to be equipped with the most efficient combustion.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the work of Nakashima et al [114], the performance of two energy technologies used for an enhanced petroleum recovery, namely, the gas lifting and the two-phase screw pumping processes are compared in light of the exergoeconomy theory. Those results have been used in turn to calculate the cumulative exergy cost and the specific CO 2 emissions of different fuels, chemicals and transportation services [115] in petrochemical refineries, biorefineries [116], fertilizers complexes [117] and even of the Brazilian electricity mix [118]. The methodology used in those studies relies on the concept of the Total Unit Exergy Cost (cT) [kJ/kJ], defined as the rate of exergy necessary to produce one unit of exergy rate (or flow rate) of a substance, fuel, electricity, work or heat comprised in the petroleum production…”
Section: Unit Exergy Cost and Co 2 Emissions Allocationmentioning
confidence: 99%